Ōhāua te Rangi and Reconciliation in Te Urewera, 1913–1983 - Webster, Steven (Waka Kuaka, 2019)
This essay is an ethnohistorical reconstruction of Tūhoe Māori cognatic descent groups (hapū) in their struggle to maintain control over ancestral lands centred around the community of Ōhāua te Rangi deep in the Urewera mountains of New Zealand. The famous social anthropologist Raymond Firth happened to visit this community when it was in the middle of these struggles in 1924, documenting one hapū and its settlement with photos. The wider context of his visit serves as a sequel illustrating the continuing interplay of Māori kinship and power in Te Urewera that was examined earlier in this journal, but in the midst of predatory rather than benevolent colonial policies. The earlier policy of 1894–1912 had established Te Urewera as a large statutory reserve under virtual Tūhoe home rule, but the Crown soon subverted the statute and attempted to obtain the entire reserve. While examination of the earlier era was guided by Eric Wolf’s theory of kinship, Marshall Sahlins’s quite different theory helps to explain an apparent paradox of tatau pounamu, the Tūhoe ideal of reconciliation between kin groups.